Sorption behavior of EE2 on soils subjected to different long-term organic amendments - Lima, Diana L. D. (2019)
The transport and fate of hydrophobic organic contaminants in the environment involve complex phenomena that are influenced by many processes that include sorption by soil components. Sorption behavior of EE2 molecules onto different soil samples was studied and results correlated with the content and type of organic matter present. The highest K value, among all soils presented in this study, was obtained for soil fertilized with compost (1.22) which presented the highest organic carbon content. Also the sorption behavior depends greatly on the soil specific organic matter characteristics. A strong positive correlation was observed between aromatic and carboxylic units and K(OC) values. The results also suggested an association of the EE2 aromatic nuclei face to face with the surface and/or another EE2 molecule and also sorbent-sorbate interactions due to hydrogen or covalent bonding, likely to occur due to the presence of phenolic function at C-3 and hydroxyl function at C-17 of the EE2 molecules that can react with carboxylic functional groups of soil organic matter. The stronger EE2 sorbs to soil organic matter lower is the leaching into drinking water resources and runoff to rivers and surface water, minimizing its residual toxicity.